Duodenal plasmacytoma: a rare extramedullary localization simulating carcinoma of the head of the pancreas. - Schoretsanitis, G. (BMJ Group, 1994)
Plasmacytomas occurring in extramedullary sites are rare tumours, particularly so when located in the gastrointestinal tract. We report the case of a solitary extramedullary plasmacytoma arising in the duodenum and simulating a carcinoma of the head of the pancreas. Diagnostic and treatment options are discussed.